2015
DOI: 10.1002/acp.3112
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Your Words and Pictures Wisely: When Do Individuation Instructions Reduce the Cross‐Race Effect?

Abstract: Recognition accuracy for faces of an individual's own race typically exceeds recognition accuracy for other-race faces. The categorization-individuation model (Hugenberg, Young, Bernstein, & Sacco, 2010) attributes this cross-race effect to motivation to encode distinctive features of own-race faces but category defining features for other-race faces. Two experiments using different stimuli tested hypotheses generated from this model with both Black and White participants. For White participants, instructions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…With even more similar faces, Sporer (1999) found an other-race effect for White German participants looking at German and Turkish faces but no other-race effect for Turkish participants. Finally, comparing Black and White faces, as in this study, Pica, Warren, Ross, and Kehn (2015) found an other-race effect for White American participants but no effect for Black participants in two studies. Most similar to this study, Wright, Boyd, and Tredoux (2003) found an other-race effect for White South African participants but not for Black South African participants, who instead showed an advantage for White faces.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…With even more similar faces, Sporer (1999) found an other-race effect for White German participants looking at German and Turkish faces but no other-race effect for Turkish participants. Finally, comparing Black and White faces, as in this study, Pica, Warren, Ross, and Kehn (2015) found an other-race effect for White American participants but no effect for Black participants in two studies. Most similar to this study, Wright, Boyd, and Tredoux (2003) found an other-race effect for White South African participants but not for Black South African participants, who instead showed an advantage for White faces.…”
Section: Discussionsupporting
confidence: 65%
“…Black South African participants tended to be more disadvantaged economically than the White Australian participants were, relative to the other-race within the study. This imbalance may have important social and perceptual consequences: as hypothesised by several authors, disadvantaged groups will likely have more motivation to recognise advantaged groups (White people in this case) than the other way around, since their livelihood may well be dependent on it (see Losin, Cross, Iacoboni, & Dapretto, 2014; Malpass, 1990; Pica et al, 2015). These factors are, however, all more relevant to race group membership than to university affiliation.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that people are in principle able to recognise own-and other-race faces similarly well, but per default do not process other-race faces in sufficient detail (Hugenberg et al, 2010). As a qualification to these initial findings, however, others have found these instruction effects to depend on expertise (Pica, Warren, Ross, & Kehn, 2015;Young & Hugenberg, 2012). In these studies, participants with higher amounts of other-race contact showed a stronger decrease in the ORB after receiving individuating instructions compared to people with more limited other-race contact.…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, such effects of individuating instructions seem to depend on expertise. Accordingly, two recent studies (Pica, Warren, Ross, & Kehn, 2015; reported stronger reduction of the ORB following individuation instructions in participants with high levels of interracial contact. These results can be explained in terms of the CIM (Hugenberg et al, 2010) if one assumes that participants with more other-race contact are also more motivated to individuate other-race faces (and therefore enhanced expertise can become effective).…”
Section: Intentionally Remembering or Forgetting Own-and Other-race Fmentioning
confidence: 94%